Understanding pregnant smokers’ adherence to nicotine replacement therapy during a quit attempt: a qualitative study - Bowker, Katharine; Campbell, Katarzyna; Coleman, Tim; Lewis, Sarah (Oxford University Press, 2015)
Background: Pregnant smokers may be offered nicotine replacement therapy (NRT) alongside behavioral support to assist with a quit attempt. Yet trials of NRT have found adherence to be low among pregnant women, and this has made it difficult to determine the efficacy of NRT. The aim of this study is to understand the experience of pregnant women who use NRT but discontinue this early or do not use the medication as recommended.